(untitled) (Medical Forum Monthly, 2024)
Background. Different drugs have been used in the past during Ramazan Sharif with none of them shown to be Gold standard. Recent data has shown DPP-IV inhibitor, sitagliptin/ metformin combination leads to less hypoglycaemic episodes when compared to sulphonylurea drug glimipride. Data is lacking from Azad Kashmir about the efficacy of these drugs during Ramazan sharif. Study Design: Randomized controlled study Place and Duration of Study: This study was conducted at Cardiac Outdoor, at District Head Quarters Hospital Teaching Hospital Mirpur Azad Kashmir in Ramazan Sharif the holy month of Islamic calendar during August 2011. Materials and Methods: Those patients included in this study who were well controlled on diet and oral drugs, no acute illness, adults more than 30 years, Type II diabetes, Both Genders those who gave consent and Baseline HBA 1c <10. Results: Patients using sitagliptin/ metformin combination had less episodes of hypoglycaemia than glemipiride. Conclusion: DPP-Iv inhibitors sitaglipitin/ metformin combination is better tolerated than glemipiride during Ramazan Sharif